Quantitative magnetic resonance angiography to assess post embolization hemodynamics following pipeline embolization. Issue 2 (April 2022) - White, Timothy G; Ryu, Brendan; Shah, Kevin A; Turpin, Justin; Black, Karen; Link, Thomas; Dehdashti, Amir R; Katz, Jeffrey M; Woo, Henry H
Introduction: Delayed intraparenchymal hemorrhage is a known complication of the Pipeline Embolization device (PED); however, its etiology is unclear and some have suggested it is a flow related phenomenon. Quantitative magnetic resonance angiography (QMRA) serves as a powerful tool to collect and analyze hemodynamic data. We report a detailed characterization of short-term hemodynamics after PED placement. Methods: Patients who underwent PED placement for a distal internal carotid artery (ICA) aneurysm between 2017 to 2019 with post embolization QMRA were reviewed. Aneurysm characteristics, flow volume rate (ml/min), mean, systolic, and diastolic flow velocities (cm/s), vessel diameter (mm), pulsatility index, Lindegaard ratio, and wall shear stress (WSS) were collected. Results: A total of 67 patients were included. Post-procedure patients were found to have a significantly lower ICA flow on the side with flow diversion when compared to the side without flow diversion (218 vs. 236.3; P < 0.05). Average ICA flow after flow diversion for aneurysms >2 cm was significantly lower when compared to the untreated side (187.7 vs. 240.4; P < 0.05). There was no difference in MCA or ACA flow or velocity. WSS was significantly lower in the treated ICA (8.2 vs. 9.0; P < 0.05). Lindegaard ratio was not different in the treated vs. contralateral untreated sides. Conclusion: PED placement for distal ICA aneurysms results in lower flow, mean velocity, and WSS when compared to the contralateral untreated ICA. This is not demonstrated distal to the Pipeline device in the ACA or MCA territories. Ultimately these findings suggest hemodynamic changes are not a cause of PED complications.